Pandemic panic and the culture of complacency - Brian J Ford (Journal of Biology and Medicine - Peertechz Publications, 2022)
The many legacies bequeathed to us by the COVID-19 pandemic have embraced novel approaches to vaccine development, a greater awareness of the principles of hygiene among the general public, the need for governments to take a proactive stance when faced with unfamiliar pathologies, and the role of specialist medical and scientific advisers. However, many of the claimed protocols are medieval in nature and have little scientific evidence to support their introduction. Similarly, we have failed to grasp the importance of the anti-vaccination campaigns, which are always founded on ignorance or willfulness, but on previous examples of duplicitous behavior by those in authority, coupled with our poor understanding of the way virus variants function, have engendered a sense that many of the precautions taken may have been unnecessary (Ford, 2020a). In consequence, I fear that future threats from hemolytic viruses of high transmissibility may be met with complacency. Improved public education, and greater academic transparency concerning the nature of risk, will be necessary if a future pandemic is to be effectively controlled.